The Effectiveness of Canva Media on Learning Outcomes in English for The Food and Drink Material for Grade 5 of SDN 13 Rantau Bayur - Aelista Dwi Wahyuni; Masagus Firdaus (Jurnal Pendidikan dan Sastra Inggris, 2025)
English is considered a universal language because it is used as the main language by many countries around the world. The use of Canva media in English learning is necessary so that students are better able to master the material being delivered and so that learning activities become more interactive. The aim of this research is to review theories related to the utilization of Canva in English learning, particularly on the topic of food and beverages for fifth-grade elementary school students. The research process was carried out through several stages, namely: (1) designing the topics to be discussed, (2) collecting literature sources relevant to the topic, and (3) extracting data from these sources as the basis for preparing the discussion and drawing conclusions.